PERANCANGAN SISTEM INFORMASI PENDAFTARAN DAN PEMBAYARAN RAWAT JALAN BERBASIS WEBSITE DI RUMAH SAKIT AMC BANDUNG - Ana Maesaroh; Topan Trianto (Universitas Ma'soem, 2018)
In the preparation of this thesis, the authors do research About Registration and Outpatient payment at RS AMC Bandung. According to the researchers, these activities have not been supported by a supportive system so that there are some obstacles such as the occurrence of registration queue, inefficient in serving outpatients. AMC Hospital as one of the public service institutions in the health sector requires the existence of an accurate, reliable, and sufficient information system to improve its services to patients and other related environments.To overcome these problems, the authors designed an information system that can be used to facilitate the data processing of outpatients at the Hospital RS AMC, the method used in designing this system is the method RUP (Rational Unifed Process). RUP (Rational Unifed Process) is a software engineering method developed by collecting various best practices in the software mining industry, where the development tools use UML (Unified Modeling languange).Thus, based on the system that has been created, it can facilitate the registration of patients who can be accessed anywhere, can improve information services for patients who will register and can expand the reach of information.